Highly efficient generation of narrow-band single-mode photon pairs from a whispering gallery mode resonator - Förtsch, Michael; Schunk, Gerhard; Josef Fürst; Strekalov, Dmitry; Gerrits, Thomas; Stevens J., Martin J.; Sedlmeir, Florian; Schwefel G.L., Harald G.L.; Nam, Sae Woo; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2014)
We present a highly efficient narrow-band pair-photon source based on a crystalline whispering gallery mode resonator, which emits photons in exactly one spatiotemporal mode. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05